2014
DOI: 10.1002/jbm.b.33269
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion and integration of tissue engineered cartilage to porous polyethylene for composite ear reconstruction

Abstract: The objective of this study was to assess the ability of tissue engineered cartilage to adhere to and integrate with porous polyethylene (PPE) in vivo and to evaluate the biomechanical integrity of the bond formed at the interface. Porcine auricular, articular, and costal chondrocytes were suspended in fibrin gel polymer and placed between discs of PPE to form tri-layer constructs. Controls consisted of fibroblasts suspended in gel or gel alone between the discs. Constructs were implanted into nude mice for 6,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 38 publications
1
10
0
Order By: Relevance
“…In literature, reports of quantitative mechanics for TE constructs are given for confined compression (Chang et al, 2003;Reiffel et al, 2013), unconfined compression (Ting et al, 1998) and tension (Isogai et al, 2005;O'Sullivan et al, 2014). While no comparison can be made with tension, the indentation results in this study E eq compare well with compressive equilibrium or apparent modulus in literature.…”
Section: Discussionsupporting
confidence: 76%
“…In literature, reports of quantitative mechanics for TE constructs are given for confined compression (Chang et al, 2003;Reiffel et al, 2013), unconfined compression (Ting et al, 1998) and tension (Isogai et al, 2005;O'Sullivan et al, 2014). While no comparison can be made with tension, the indentation results in this study E eq compare well with compressive equilibrium or apparent modulus in literature.…”
Section: Discussionsupporting
confidence: 76%
“…19 Porous polyethylene can also be used as a skeletal framework for tissue engineered-cartilage to adhere and integrate into. O'Sullivan et al 30 demonstrated that porous polyethylene with surrounding porcine auricular chondrocytes showed consistent neocartilage integration. The tensile strength of the auricle made from this neocartilage-enforced Medpor framework was superior to that of a normal Medporreconstructed auricle.…”
Section: Skin Graft Harvest and Preparationmentioning
confidence: 99%
“…The tensile strength of the auricle made from this neocartilage-enforced Medpor framework was superior to that of a normal Medporreconstructed auricle. 30…”
Section: Skin Graft Harvest and Preparationmentioning
confidence: 99%
“…Heatmap representing the proportion of publications by year that utilized specific translational research methodologies from construct characterization to human trial to investigate otologic tissue engineering 15,25‐35,38‐43,45,46,107‐144 …”
Section: Discussionmentioning
confidence: 99%